Both decreasing interstructural space size and increasing total cover increase shrimp abundance on artificial structures deployed in a UAE seagrass bed - Bartholomew, Aaron (2015)
We tested whether total cover and interstructural space size affect the abundances of mobile fauna colonizing small artificial structures deployed in a seagrass bed near Dubai, UAE, during May and September 2011. There were three complexity treatments: low cover with wide interstructural space sizes, high cover with wide space sizes, and high cover with narrow space sizes. This is the first study to deploy structures that vary interstructural space size while keeping cover constant and that vary cover while keeping interstructural space size constant. Shrimp had significantly higher abundance in the high cover/narrow space treatment compared with the low cover/wide space treatment. Complexity did not affect the abundances of most fauna. There were differences in the abundances of nudibranchs, amphipods, cumaceans, fish, shrimp, isopods, and crabs between the two deployment times. This is the first study demonstrating possible seasonal differences in UAE seagrass fauna.